2016
DOI: 10.3103/s1063455x16050040
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing linear alkyl benzene sulfonate removal using Fenton oxidation process in Taguchi Method

Abstract: Linear alkyl benzene sulfonate (LAS), which is the most common used anionic surfactant in detergents manufacturing, can discharge onto water resources through wastewater and causes change in taste and odor, disruption in water treatment processes, aquatics death, and oxygen transfer limitation. Accordingly, this article investigates to optimize LAS removal using Fenton oxidation process in Taguchi Method for the first time. LAS removal using Fenton oxidation was perused experimentally in a lab-scale reactor. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results of this study were compared with literature about the detergent degradation by advanced oxidation processes. Khorsandi et al reported LAS concentration decrease from 25 to 3.38 mg L −1 with Fenton oxidation (900 mg L −1 hydrogen peroxide, 170 mg L −1 ferrous ion, pH 4 and a reaction time of 120 min). They showed that LAS degradation by Fenton oxidation has apparently high efficiency but the low COD degradation efficiency corresponding to LAS indicates its incomplete decomposition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study were compared with literature about the detergent degradation by advanced oxidation processes. Khorsandi et al reported LAS concentration decrease from 25 to 3.38 mg L −1 with Fenton oxidation (900 mg L −1 hydrogen peroxide, 170 mg L −1 ferrous ion, pH 4 and a reaction time of 120 min). They showed that LAS degradation by Fenton oxidation has apparently high efficiency but the low COD degradation efficiency corresponding to LAS indicates its incomplete decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…[1] There are many studies in the literature about the treatment of surfactants such as adsorption, [2,3] electrochemical coagulation, [4] electrochemical oxidation, [5] photochemical treatment, [6] sonication, [7] wet air oxidation, [8] photodegradation and ozonation, [9] anaerobic degradation, [10,11] functionalized multi-walled carbon nanotubes, [12] photosynthesis, [13] combined electrochemical and photocatalytic process, [14] and Fenton oxidation. [15] The number of studies on the degradation of LABSA using the sonication process is limited. Ultrasonic energy produced by sound waves, which are out of hearing range (20 kHz to 500 MHz), has been used commonly in the fields of engineering, science and medicine for many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation